Generic Medicine Pricing Policies in Europe: Current Status and Impact - Dylst, Pieter (Molecular Diversity Preservation International, 2010)
Generic medicine pricing is an area of national responsibility of European Union countries. This article aims to present the current status and impact of generic medicine pricing policies in ambulatory care in Europe. The study conducts a literature review of policies relating to free-pricing systems, price-regulated systems, price differentiation, price competition and discounts, and tendering procedures; and a survey of European generic medicine pricing policies. Competition from Indian generic medicine manufacturers, European variation in generic medicine prices and competition between generic medicine manufacturers by discount suggest that the potential savings to health care payers and patients from generic medicines are not fully realized in Europe. One way of attaining these savings may be to move away from competition by discount to competition by price. Free-pricing systems may drive medicine prices downwards under specific conditions. In price-regulated systems, regulation may lower prices of originator and generic medicines, but may also remove incentives for additional price reductions beyond those imposed by regulation. To date, little is known about the current status and impact of tendering procedures for medicines in ambulatory care. In conclusion, the European experience suggests that there is not a single approach towards developing generic medicine pricing policies in Europe.